Concept of “Me” and “Others” in al-Qur’an Perspective - Muhammad Aniq Imam Muh. Syaifudin (Pascasarjana Universitas Wahid hasyim Semarang, 2017)
AbstractThe goal of this study is effort to disclose the real image ofislamic teaching particularly its attitude toward others, peaceand dialogue not conflict and is the starting point of mosleminteraction toward others for solving the problems and bringthe point of view close.Keywords: the Qur’an; concept of me and others,tolerance; islamic teaching